Tumor necrosis factor signaling requires iRhom2 to promote trafficking and activation of TACE - Adrain, Colin (2012)
The cytokine tumor necrosis factor (TNF) is the primary trigger of inflammation. Like many extracellular signaling proteins, TNF is synthesized as a transmembrane protein; the active signal is its ectodomain, which is shed from cells after cleavage by an ADAM family metalloprotease, TACE/ADAM17. We report that iRhom2/RHBDF2, a proteolytically inactive member of the rhomboid family, is required for TNF release in mice. iRhom2 binds TACE and promotes exit from the endoplasmic reticulum. The failure of TACE ER exit in the absence of iRhom2 prevents furin-mediated maturation and its trafficking to the cell surface, the site of TNF cleavage. Given the role of TNF in autoimmune and inflammatory diseases, iRhom2 may represent an attractive therapeutic target.